2016
DOI: 10.1016/j.actatropica.2015.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Neurocysticercosis-related mortality in Brazil, 2000–2011: Epidemiology of a neglected neurologic cause of death

Abstract: Neurocysticercosis (NCC) is an important cause of severe neurological disease mainly in low- and middle-income countries, but data on NCC mortality from endemic areas are scarce. Here we analysed the epidemiological patterns of NCC-related mortality in Brazil. We included all deaths recorded in Brazil between 2000 and 2011, in which NCC was mentioned on death certificates, either as underlying or as associated cause of death. NCC was identified in 1829/12,491,280 deaths (0.015%), 1130 (61.8%) as underlying cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 63 publications
(102 reference statements)
1
26
0
Order By: Relevance
“…Regarding mortality, a study undertaken in Brazil reported that cysticercosis was identified in 0.016% of all deaths during 2000–2011, and NCC was reported in 91.1% of those deaths due to cysticercosis [46]. The number of deaths due to NCC in our country is unknown, but it supports the idea that we are in risk of death, given the number of cases reported during the study period.…”
Section: Discussionsupporting
confidence: 68%
“…Regarding mortality, a study undertaken in Brazil reported that cysticercosis was identified in 0.016% of all deaths during 2000–2011, and NCC was reported in 91.1% of those deaths due to cysticercosis [46]. The number of deaths due to NCC in our country is unknown, but it supports the idea that we are in risk of death, given the number of cases reported during the study period.…”
Section: Discussionsupporting
confidence: 68%
“…The observed findings indicate gender-specific patterns of infectious disease exposure, as the relationship between gender and risk of infection is often conditioned by different socioeconomic, environmental, occupational, and behavioral factors, as well as access to healthcare services [ 10 , 36 , 37 , 40 ]. In fact, healthcare seeking behavior in Brazilian males is more often retarded, with increased morbidity and severity for some diseases [ 39 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the impact of control measures implemented in recent decades, other NTDs with high mortality impact, such as schistosomiasis and leprosy, also presented decreasing trends, as shown previously ( Martins-Melo et al, 2015a , Martins-Melo et al, 2014a , Amaral et al, 2006 ). Other factors not related to specific control programmes may have contributed to the decline in morbidity and mortality, such as increased urbanization, general improvements in housing, socioeconomic and sanitary conditions, and improved access to healthcare services ( Martins-Melo et al, 2012a , Martins-Melo et al, 2014a , Martins-Melo et al, 2016b ).…”
Section: Discussionmentioning
confidence: 99%
“…While the analysis of underlying causes of death is usually applied as standard, an analysis of multiple causes of death (i.e. underlying and associated causes of death) will facilitate trend and spatial analyses, besides the inclusion of information on NTDs that are usually not selected as an underlying cause of death ( Martins-Melo et al, 2012a , Martins-Melo et al, 2015a , Martins-Melo et al, 2014a , Martins-Melo et al, 2016b ). Knowledge of the geographical distribution and trends of NTD-related deaths in endemic countries is essential for monitoring and evaluation of the impact of disease prevention and control intervention strategies, and the effectiveness of disease-specific control measures ( Martins-Melo et al, 2012a , Martins-Melo et al, 2014a , Martins-Melo et al, 2014b ).…”
Section: Introductionmentioning
confidence: 99%